PROBLEM SOLVING IN PSI - Webber, M. E.; Fuller, O. M. (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1973)
The Personalized System of Instruction, devised by Keller and Sherman in the 1960’s, is a course format that has been winning wide acceptance among university teachers in the past few years. In this article we indicate the main advantages that we see in the format, the modifications that we have made to adapt it to our needs, and some of the resulta obtained by using a modified PSI format in two engineering courses.